Cultivating Hope Among Medically Traumatized Older Adults: A Narrative Perspective - Heitmann, Danielle (Lumen et Vita, 2015)
The sudden need for hospitalization and/or surgery among older adults after a fall can often be discussed by many in the medical profession as the beginning of a series of negative sequelae that may eventually lead to the end of one's life -- or at least the end of one's life as he or she currently knows it. This experience of a fall among this age group can be quite traumatizing, interrupting many of the stories the person has previously held about his or her ability, health and functional capacity. However, narrative informed practice would raise questions regarding the pathology-based discourse that surrounds the patient during hospitalization and rehabilitation in terms of how these stories may serve to label people and diminish hope. Pastoral care for the client in the hospital who has experienced such a shock at this age requires a unique sensitivity. A powerful intervention in this space may prove to be critical to the overall recovery and wellbeing of older adults following such a life event. In particular, proponents of narrative therapy would offer key techniques to specifically interrupt the dominant discourse surrounding falls in order to cultivate hope for recovery among this population. While narrative therapy has been studied across the life course, this paper would examine the particular context of the older adults after falls, hospitalization and/or surgery. In doing so, it intends to examine patient narratives and pastoral care research to identify short-term counseling interventions that promote hope, resiliency, and recovery among this population.